Study on Implementation of Integrated Curriculum in Indonesia - Erwin Akib; Muhammad Erwinto Imran; Saiyidah Mahtari; Muhammad Rifqi Mahmud; Anggy Giri Prawiyogy; Irfan Supriatna; MT. Hartono Ikhsan (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
An integrated curriculum is an educational approach that prepares students to face lifelong learning. In curriculum integration, schools must view education as a process of developing the abilities needed in life, especially in facing 21st-century life challenges, not discrete subjects that are divided into different fields. Integrated learning will provide the opportunity for students to understand the complex problems that exist in the surrounding environment with a complete view. With this integrated learning, students are expected to have the ability to identify, gather, assess, and use information that is around them meaningfully. This can be obtained not only through the provision of new knowledge to students but also through the opportunity to strengthen and apply it in a variety of increasingly diverse new situations. The main focus of this article is to analyze the implementation of integrated learning in the curriculum in Indonesia. The integrated curriculum developed by Robin Fogarty has many advantages that can be adapted in the development of education in Indonesia, including the revised Curriculum 2013. Academics and practitioners must comprehensively understand the nature of the ten curriculum models (Robin Fogarty) and Curriculum 2013 before making tools and implementing them in learning.